Central nervous system infection with Acanthamoeba in a malnourished child. (24th October 2012) - Khurana, Sumeeta; Mewara, Abhishek; Verma, Sanjay; Totadri, Siddharth K
Abstract : A 3-year-old male child presented with moderate-to-high grade fever and non-projectile vomiting, generalised seizures and altered sensorium for 1 month. CT scan revealed a communicating hydrocephalus with no basal exudates. The microbiological tests were negative for Streptococcus pneumoniae, Haemophilus influenzae, Neisseria meningitides, brucellosis, cryptococcosis, HIV and Mycobacterium tuberculosis . Intracranial pressure was relieved by ventriculo-peritoneal shunt, and the child was empirically started on ceftriaxone, and antitubercular therapy with isoniazid, rifampicin, ethambutol and streptomycin, along with steroids and supportive treatment for seizures. The symptoms persisted. On further investigation the cerebrospinal fluid showed growth of Acanthamoeba spp., following which the initial treatment was stopped and a combination antiamoebic regimen of cotrimoxazole, rifampicin and ketoconazole was started, after which he showed clinical improvement. The treatment was continued for 6 months and on follow-up at 1, 3 and 6 months, there was a remarkable clinical improvement with no residual symptoms.